Ztracený řád: Španělský Odinismus mezi mýtem a modernitou - Putera, Sarah Matilda (Lidé města, 2025)
This article explores the Spanish Odinist movement Comunidad Odinista de España – Ásatrú (COE) and its engagement with history, myth, and literature while shaping religious and cultural identity. Drawing on textual and ethnographic analysis, the study examines how COE links spiritual orientation with ritual practice, ethical values, landscape, and communal life. The movement is interpreted as an expression of contemporary efforts to find meaning and rootedness, drawing on Old Norse tradition and adapting it to the conditions of the modern world. The article highlights how a contemporary religious movement can shape a sense of continuity with the past through narrative, ritual, and symbolism.